Controlling light on the other side of frosted glass - Wong, Felicia Zheng Mun (2017)
This report will discuss in detail the implementation of a feedback-based phase modulation method to obtain the optimum incident wavefront is by exploiting iterative optimization algorithms. In particular, the optimization technique focused on and demonstrated with will be the genetic algorithm. The description of the construction of a feedback algorithm based on a model genetic algorithm for phase optimization and the logic behind it will be detailed in the report. Subsequently, the simulation results for the successful construction of the algorithm as well as the implementation on the actual experiment set up will be shared in the report. The hardware components used in the implementation include a He-Ne laser of λ=632.8, a Spatial Light Modulator (SLM) and a diffuser. Observations and conclusions drawn based on the simulation and actual experiment shall be described in further detail.